Optimizing interagency coordination and supervision in corruption eradication efforts - Heryadi, Dudy; Sukmawan, Denny (Integritas: Jurnal Antikorupsi, 2023)
This article delves into the coordination and supervision efforts of the Corruption Eradication Commission (KPK) with regional governments, the police, and the prosecution agencies. Such responsibilities are stipulated in Law No. 19 of 2019 on the KPK. In general, our findings indicate that the utilization of MCP, JAGA, and e-SPDP applications has not been optimized as means of coordination and supervision. Furthermore, we identify that coordination and supervision with regional governments can be enhanced through Satgas Wilayah. While the coordination and supervision with the police and attorney can be concentrated on efforts to harmonize the issuance of SP3 and activities related to oversight, research, and the assessment of needs within the KPK, police, and prosecution agencies. Throughout the data collection and analysis process, we also identify substantial weaknesses in the publication of annual reports by the KPK and the Indonesian Corruption Watch (ICW) to the public. This research adopts a descriptive method, guided by the theory of interagency coordination and supported by secondary data from the annual reports of the KPK and ICW, as well as transcripts of proceedings at the Constitutional Court (MK).
Keywords: Police; Attorney